Analisa Pengaruh Insentif, Upah dan Absensi pada Produktifitas Karyawan Mulia Bordir di Blitar Studi pada Bisnis Keluarga di Kec. Kepanjenlor Desa Kauman Blitar - Sunarsasi Sunarsasi (Akutansi Bisnis & Manajemen ( ABM ), 2017)
All are engaged in either form of a company or organization would want corresponding results. These results are obtained from the productivity of its employees where the employee also wants incentives or salaries and wages and fair. To achieve this company create and develop the system of incentives, wages and absenteeism as a gift and tailored to the type of work in the company in accordance with applicable regulations. So also on the size of the incentives and wages adjusted for absences. For this study authors used multiple regression quantitative methods. From the results say that the independent variable in quantity multiple regression are incentives, wages and absenteeism, while the dependent variable is productivity.